Effectiveness of Cognitive Behavioral Therapy for Insomnia on Sleep Quality in Patients with Insomnia: A Meta-Analysis - Cynthia Octaviani; Hanung Prasetya; Bhisma Murti (Indonesian Journal of Medicine, 2023)
Background: The relationship between sleep quality and sleep quantity is very close and has a significant impact on a person's sleep needs. If someone does not get enough sleep, then this will have an impact on the quality of their sleep, and vice versa. Therefore, maintaining a good quality of sleep is very important to maintain a healthy body and improve quality of life. The aim of the study was to analyze the effect of cognitive behavior therapy for insomnia (CBT-I) on sleep quality in insomnia patients. Subjects and Method: This study is a meta-analysis with PICO. Population: insomnia patients. Intervention: given cognitive behavior therapy for insomnia (CBT-I). Comparison: not given cognitive behavior therapy for insomnia (CBT-I). Outcome: sleep quality. The articles used in this study were obtained from five databases, namely PubMed, Embase, Web of Science, ScienceDirect, and Google Scholar. The keywords used to search for articles use the medical subject heading (MeSH) term and the emtree of the keywords "Insomnia" AND "Cognitive Behavior Therapy for Insomnia" AND "Sleep Quality". The articles used were full text in English from 2013 to 2023. Articles were selected using the 2021 PRISMA flowchart and analyzed using the RevMan 5.3 application. Results: A total of 10 randomized controlled trial study articles came from Iran, Canada, Spain, Texas, Korea, Kansas and the United States. The total sample size is 473 research subjects. Based on the analysis, insomnia patients who were given CBT-I therapy showed an average PSQI score of 1.88 units lower than those not given CBT-I (placebo), and the difference was statistically significant (SMD = -1.88; 95% CI = -2.55 to -1.22; p<0.001). Then insomnia patients who were given CBT-I showed an average PSQI score of 0.52 units lower than those given other insomnia therapies, and the difference was statistically significant (SMD= -0.52; 95% CI= -0.77 to -0.28; p <0.001) . Then when viewed as a whole, it shows that insomnia patients who are given CBT-I therapy on average have or show a PSQI score of 0.78 units lower than other therapies and without CBT-I therapy (placebo), and this difference is statistically significant (SMD= -0.78; 95% CI= -1.13 to -0.42; p < 0.001). Conclusion:  Cognitive behavior therapy for insomnia (CBT-I) can improve sleep quality in insomnia patients (decrease the PSQI score). Keywords:  insomnia, cognitive behavior therapy for insomnia, sleep quality. Correspondence:  Cynthia Octaviani. Master's Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: Cynthia.octaviani14@gmail.com. Mobile: +6287812315855.